Characterization of Polycrystalline Silicon Substrates (p-Type) of Photovoltaic Use - Lounis, A.; Lenouar, K.; Gritly, Y.; Abbad, B.; Boumaour, M. (Asian Journal of Chemistry, 2010)
The quality of the material, polycrystalline silicon, is justified by the required features for the final use of the product. It is considered that this quality is due to the impurities which are present in the metal. Carbon, oxygen, boron and transition metals are catalogued among the most frequently observed impurities in silicon, because of their high mobility and solubility in polycrystalline silicon. These impurities generate a yield decrease in the photovoltaic components. The aim of this work is to determine the concentration of impurities such as carbon, iron, copper, titanium, nickel as well as some properties of the flat product such as thickness, resistance, rigidity, roughness and flatness. The dislocations density is also assessed.